Atorvastatin for unruptured intracranial vertebrobasilar dissecting aneurysm (ATREAT-VBD): protocol for a randomised, double-blind, blank-controlled trial. Issue 4 (28th April 2022) - Turhon, Mirzat; Kang, Huibin; Huang, Jiliang; Li, Mengxing; Liu, Jian; Zhang, Ying; Wang, Kun; Yang, Xinjian; Zhang, Yisen
Abstract : Introduction: Vertebrobasilar dissecting aneurysms (VBDAs) are associated with serious complications and a poor prognosis. It is believed that inflammation of the aneurysm wall may be the main cause of rupture or deterioration. Atorvastatin has been shown to inhibit inflammation and may be a suitable drug candidate. Here, we report a clinical research study protocol to investigate whether atorvastatin inhibits inflammation of the aneurysm wall, as measured by signal index enhancement. Methods and analysis: We have designed a single-centre, randomised, double-blind, blank-controlled clinical trial. 40 patients with non-ruptured VBDAs with enhancement aneurysm walls will be enrolled in Beijing Tiantan Hospital. Eligible patients will be randomly divided into two treatment groups, at a ratio of 1:1, to receive atorvastatin 20 mg orally for 6 months or no treatment. The primary assessment outcome will be the change in aneurysm wall enhancement, as measured by the signal index during the 6-month treatment period. The secondary assessment outcomes will be the aneurysm morphology (intramural haematoma, dissection valve and false lumen) and changes in the concentrations of inflammatory factors, including C reactive protein, tumour necrosis factor-α, interleukin (IL)-1β and IL-6. Ethics and dissemination: The protocol has been approved by the medical ethics committee of the Beijing Tiantan Hospital at which the work will be conducted (Approval No. KY 2019-024-02). Written informed consent will be obtained from all participants. Findings from the study will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT04943783 .